Legal Participatory Legal Counseling to Realize Sei Mencirim Village as a Region Free of Violence against Women and Children - Junaidi Lubis; Tika Rohani Zega; Delina Giawa; Alexius Saroniat Harefa; Juliya Maria (Institut Teknologi dan Bisnis Asia Malang, 2026)
Purpose: Violence against women and children in Indonesia's rural areas is frequently concealed by cultural normalization and limited access to formal legal tools. Method: This legal counseling activity was carried out in Sei Mencirim Village, Sunggal District, Deli Serdang Regency, The approach method used is counseling involving village officials, community leaders, women and the surrounding community by conducting discussions and questions and answers in accordance with the conditions of the village community. Practical Applications: Practically, this social transformation is realized through the establishment of Village Movement Cadres who actively engage in micro-sharing, safe zone mapping, and enhancing the national complaint channel, as evidenced by real case reports submitted via SAPA 129 after the activities. Conclusion: This study enhances the PAR methodology by translating formal law into local language and empowers rural Indonesian communities as active legal agents.